Communication Conduct in an Island Community - Goffman, Erving (Public Domain Series, 2022)
Canadian-born Erving Goffman (1922-1982) was the twentieth century's most important sociologist writing in English. His 1953 dissertation is published here for the first time, on the hundredth anniversary of his birth. The remarkable study, based on fieldwork on a remote Scottish island, presents in embryonic form the full spread of Goffman's thought. Framed as a "report on a study of conversational interaction," the dissertation lingers on the modest talk of island "crofters." It is trademark Goffman: ambitious, unconventional in form, and brimmed with big-picture insight. The thesis is that social order is made and re-made in communication-the "interaction order" he re-visited in a famous and final talk before his 1982 death. The dissertation is, as Yves Winkin writes in a new introduction, the "Rosetta stone for his entire work." It was here, in 360 dense pages, that Goffman revealed, quietly, his peerless sensitivity to the invisible wireframes of everyday life.